Nail features in healthy term newborns: a single‐centre observational study of 52 cases. (20th October 2016) - Chinazzo, M.; Lorette, G.; Baran, R.; Finon, A.; Saliba, É.; Maruani, A.
Abstract: Introduction: The anatomy and embryology of the nail are well known, and nail abnormalities are a feature of many genodermatoses. However, the physiological aspect is not well described. We aimed to analyse the physiological features of nails in healthy newborns. Methods: We performed an observational, prospective study at University Hospital Center of Tours between July and October 2015. Newborns were included by a dermatologist assistant during the systematic examination on release of the mother from the hospital. The medical history of the mother and infant were recorded by using a standardized questionnaire. Finger‐ and toenails were systematically photographed for a second interpretation by a dermatologist with blinding to the first photograph. Results: Fifty‐eight patients were eligible, and 52 were included. Half of the newborns were males, and the mean age at inclusion was 3.6 ± 1.2 days. Fingernails had an oval shape (71.1%) or a flat curvature (63.5%), and half had a lunula. Toenails showed an apparent hypertrophy of the proximal nail fold (38.4%) and lateral nail fold (73.1%). The shape of the nails was triangular (50.0%) or round (21.1%). We noted koilonychia in 32.7% of infants and lunula in 7.7%. Distal parts showed onychoschizia (28.8%) and onycholysis (26.9%). Conclusion: Koilonychia, onychoschizia of toenails or absence of lunula are physiological features of nails in newborns.